2013
DOI: 10.1007/s11999-012-2698-4
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femur Rotation Relates to Joint Obliquity in ACL-deficient Chinese

Abstract: Background The lower limb osteometry of Chinese differs from that of whites. The joint line of the knee in the coronal plane in Chinese is more medially inclined and the posterior condylar angle of the distal femur in the axial plane is larger. However, it is unclear whether there is any direct association between the coronal plane and axial plane osteometry. Questions/purposes We asked whether the joint line obliquity of the knee is related to the posterior condylar angle of the distal femur in young Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…[ 8 10 , 15 20 ] According to the study involving 41 cadaver measurements by Yip et al, [ 8 ] the average posterior condyle angle (PCA) of Chinese men is (5.1 ± 1.9)°, which is smaller ( P < .05) than that of Chinese women (5.8 ± 1.8)°. In consistence with this study, we calculated the mean PCA of (4.5 ± 2.5)° in men and (5.1 ± 2.5)° in women, which is different from the data of the Caucasian population [ 8 , 10 , 11 , 18 , 21 , 22 ] (Table 5 ). There are several reasons that could explain the minor difference of these angles in the same ethnic group.…”
Section: Discussionmentioning
confidence: 77%
“…[ 8 10 , 15 20 ] According to the study involving 41 cadaver measurements by Yip et al, [ 8 ] the average posterior condyle angle (PCA) of Chinese men is (5.1 ± 1.9)°, which is smaller ( P < .05) than that of Chinese women (5.8 ± 1.8)°. In consistence with this study, we calculated the mean PCA of (4.5 ± 2.5)° in men and (5.1 ± 2.5)° in women, which is different from the data of the Caucasian population [ 8 , 10 , 11 , 18 , 21 , 22 ] (Table 5 ). There are several reasons that could explain the minor difference of these angles in the same ethnic group.…”
Section: Discussionmentioning
confidence: 77%
“…Moon et al and others have noticed that gap balancing technology leads to more external rotation than measured resection technology [ 29 , 30 ]. In addition, Yau et al [ 31 ] reported larger medially inclined (5° ± 3°) and posterior condyle angles (5° ± 2°) of the knee for Chinese patients than for Caucasians. From this, we infer that this is also one of the reasons for the increase in the femoral external rotation in the GB group.…”
Section: Discussionmentioning
confidence: 99%
“…Greater tibial varus is observed in the Asian population while external tibial rotation and a statistical difference in translation are found in the Caucasian population. Except for different protocols, these differences are attributed to the differences in the anatomy of the intercondylar notch, mechanical axis, and tibiofemoral alignment [ 33 ]. A higher quadriceps angle (Q-angle), varus alignment, and abnormal lower limb mechanical axis, including knee recurvatum, excessive navicular drop, and excessive subtalar pronation, are anatomic malalignments related to increased risk of ACL injury [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher Q-angle places the knee at risk of static and dynamic valgus stress [ 23 ]. The lower limb alignment is more varus, and the knee is medially inclined in the Chinese population when compared to the Caucasian population [ 33 ]. Our observations of greater tibial varus are compatible with these findings.…”
Section: Discussionmentioning
confidence: 99%